Tinker trak: Revolutionizing education - Uribe, Diego (Base Diseño e Innovación, 2016)
Tinker Trak is an educational laboratory that seeks to develop the creativity and ability of doing of boys and girls by creating opportunities of playing, imagining and learning by doing. The idea is not transferring curricular content following the demands of the Ministry of Education, but rather have the students integrate those contents through a memorable experience.